European integration and the incompatibility of national varieties of capitalism problems with institutional divergence in a monetary union - Alison Johnston; Aidan Regan (Max Planck Institute for the Study of Societies, 2014)
Recent literature on the European debt crisis emphasizes that rising external trade and lending imbalances between the European Monetary Union's (EMU) Northern and Southern member states served as a crucial determinant behind speculative divergence between these two regions. However, these gaping external imbalances only emerged with the launch of the single currency. In this paper, we examine how three different currency regimes - monetary union, fixed exchange rate, and flexible exchange rates - influence the mutual co-existence of export-led growth models (which predominate in the Eurozone's crisis-spared Northern economies) and domestic demand-led growth models (which predominate in the Eurozone's crisis-prone Southern economies). We hypothesize that external imbalances between these two growth models did not emerge prior to EMU because of the presence of two adjustment mechanisms in the real exchange rate: the nominal exchange rate (in soft currency regimes) and the promotion of inflation convergence by national central banks (in hard currency regimes). European monetary integration removed these two readjustment mechanisms, leading to a persistent divergence in the real exchange rate and ultimately to external imbalances between Europe's diverse models of capitalism. – – In der neueren Literatur zur europäischen Schuldenkrise wird betont, dass die zunehmenden Ungleichgewichte im Leistungs- und Kapitalverkehr zwischen den nördlichen und südlichen Mitgliedstaaten der Eurozone ein entscheidender Faktor für den stark unterschiedlichen Spekulationsdruck der Investoren auf diese Regionen waren. Jedoch traten diese massiven außenwirtschaftlichen Ungleichgewichte erst mit der Einführung der Gemeinschaftswährung auf. Das Discussion Paper untersucht, wie der Kontext des Währungsregimes - unterschieden werden die Währungsunion, das feste und das flexible Wechselkursregime - das Zusammenwirken der exportgetriebenen Wachstumsmodelle (vorherrschend im von der Krise vergleichsweise wenig betroffenen Norden Europas) und der binnenorientierten Wachstumsmodelle (vorherrschend im von der Krise vergleichsweise stark betroffenen Süden Europas) beeinflusst hat. Dabei wird die Hypothese aufgestellt, dass vor dem Inkrafttreten der Europäischen Währungsunion keine außenwirtschaftlichen Ungleichgewichte zwischen diesen Wachstumsmodellen auftraten, da es zwei Mechanismen zur Anpassung des realen Wechselkurses gab: die nominale Abwertung (genutzt vor allem von Weichwährungsländern) und die von den nationalen Zentralbanken herbeigeführte Inflationskonvergenz (in Hartwährungsländern). Mit der europäischen Währungsintegration wurden diese beiden Mechanismen außer Kraft gesetzt, was eine anhaltende Divergenz der realen Wechselkurse und schließlich außenwirtschaftliche Ungleichgewichte zwischen den verschiedenen Kapitalismusmodellen in Europa zur Folge hatte.
Keywords: 300